Die invloed van die Aristoteliesskolastieke filosofie op die Dordtse Leerreëls (1619): ? Christelik-filosofiese analise (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2012)
Some Reformed theologians have already suggested that aspects of Aristotle’s philosophy may have played a role in the formulation of the Canons of Dordt. However, as theologians they could not provide a full picture of philosophical presuppositions of this confession, still accepted by many Reformed churches worldwide. Further more, some of these scholars have tended to view Dordt as atriumph of Aristotelian Scholasticism, while others have called such a conclusion into question. What was the real state of affairs?This contribution, therefore, takes up the issue again, but this time from an explicitly Christian-philosophical perspective. The leading question will be to what extent the scholastic philosophical orientation at Dordt affected the (theological) content of the Canons. Did this kind of philosophy render a positive service to Reformed theo logy, was it detrimental, or was it merely a matter of style that left the Canons’ contents basically unaffected? The investigation develops as follows: The first, general and introductory section includes the following subsections. First, the basic question is asked whether and how the Canons were philosophically influenced. Then the central problem at Dordt is identified, viz. the relationship between God and the human being. Next two scholastic methods, current at the time, are described. Some remarks about the use of the Scriptures in the Canons follow. Finally a brief overview of subsequent theological reflection on the Canons is given. The second main part provides a brief characterisation of scholastic thinking at the time of Dordt. The third main section contains a detailed analysis of all five chapters of the Canons. It indicates the presence of scholastic philosophy in general and a decretal theology built on a synthetic interpretation of especially Aristotle’s philosophy. Part four returns to the two main conflicting viewpoints at the Synod and its final adoption of a late-medieval solution. Then it indicates the similarity between the Canons and the “Synopsis Purioris Theologiae”, published at the request of the Synod six years afterwards in 1625.Since the problem of the relationship between divine sovereignty and human responsibility was not satisfactorily solved in the Canons, two questions are finally asked. The first is about contem porary (Reformed) Christians’ attitude towards the Canons. The second is whether a Reformational Christian philosophy may be able to make a contribution towards solving the age-old and vexing problem of divine sovereignty and human responsibility.